Expression of cyclooxygenase-2 and matrix metalloproteinase-2 in adenomyosis and endometrial polyps and its correlation with angiogenesis - Tokyol, Cigdem; Aktepe, Fatma; Dilek, Fatma Hüsniye; Sahin, Onder; Arioz, Dagstan Tolga (International journal of gynecological pathology, 2009)
This study investigates the expression of cyclooxgenase (COX)-2 and matrix metalloproteinase (MMP)-2 in patients with adenomyosis or endometrial polyps and their possible relation to microvascular density in these lesions. The subjects were 25 patients with adenomyosis, 30 patients with endometrial polyps, and 20 female controls. The expression of COX-2, MMP-2, and CD34 was studied immunohistochemically. Microvesseldensity (MVD) was calculated by the counting of CD34-positive vascular endothelial cells. The quantity and intensity of COX-2 expression in endometrium did not vary during the menstrual cycle in the control group and in patients with endometrial polyps. In patients with adenomyosis, it was higher in the secretory phase. MMP-2 expression in stromal cells in adenomyotic foci and endometrial polyps were higher than in normal endometrium. In the proliferative phase, MVD in adenomyosis foci was higher than in normal endometrium and endometrial polyps. In the secretory phase, MVD in adenomyotic foci and endometrial polyps was higher than in normal endometrium. Overexpression of stromal MMP-2 may play a role in the development of adenomyosis and endometrial polyps. Aberrant COX-2 expression in eutopic endometrium during the luteal phase may be associated with the pathogenesis of adenomyosis; however, expression of COX-2 does not seem to play a role in the development of endometrial polyps. MVD was high in both lesions, but there was no significant correlation between MVD and the expression of MMP-2 or COX-2. Mechanisms other than COX-2 and MMP-2 may contribute to the promotion of angiogenesis in these lesions.